PATTERNS RIGHT AMOUNT DIET, SCHEDULE, AND THE BLOOD SUGAR OF PATIENTS WITH DIABETES MELLITUS INSTALLATION OF TYPE II IN OUT PATIENT - Suprihatin, Suprihatin; Susilo Putro, Prayugo Juwi (Jurnal Penelitian STIKES Kediri, 2012)
Diabetes mellitus type II is a chronic disease that occurs when the pancreas produces enough insulin but the body can not effectively use it. It results from patientâ€™s unhealthy eating habits. High blood sugar on Diabetes mellitus type II patient will trigger complications.Â The design used in the study was correlational Analytical. The population was patients with type II diabetes mellitus on outpatient installation Baptist Kediri Hospital. Using Accidental Sampling Technique, it was obtained 60 respondents who met the inclusion criteria. The independent variables were correct amount diet, schedule, and type. The dependent variable was the fasting blood sugar. The data were collected using structured interviews and observation sheet. Those were analyzed using Multiple Regression tests with significance level Î± â‰¤ 0.05. The results showed the right amount of diet has a strong relationship with fasting blood sugar levels (p = 0.000), while the exact schedule of diet does not have a strong relationship with fasting blood sugar levels (p = 0.247), as well as the right kind of diet do not have a strong relationship with fasting blood sugar levels (p = 0.432). The conclusion of this research is no precise relationship of diet pattern, timetables, and types of blood sugar levels of patients with diabetes mellitus type II in the hospital outpatient installation Kediri Baptist Hospital.